Multilingualism, language contact and translation in Walter Scott’s Scottish novels - Toda, Fernando (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
In his Scottish novels, Walter Scott foregrounded the multilingual and multidialectal situation of Scotland. He not only made a deliberate effort to reflect the different linguistic varieties in the dialogues, but also, through his narrators, drew his readers’ attention to the variety being used or the pronunciation employed. Since Scott is writing about post- Union Scotland, he implies that the United Kingdom is a multilingual and multicultural society, and that the British have to be aware of this in order to make their union stronger in its diversity, by preserving national cultural identities and values. Evidence is given from three of Scott’s most relevant Scottish novels.